CHARACTER CHANGE OF THE MAIN CHARACTER IN OLIVER BOWDENS ASSASSINS CREED: FORSAKEN - Saskya Rohima Anggraeni; Shita Dewi Ratih; Agnes Setyowati (Universitas Pakuan, 2022)
The topic of this research is related to the character change experienced by the main character in the novel Assassins Creed: Forsaken by Oliver Bowden. This research uses the descriptive analysis research method with the literature study technique which produces findings in the form of intrinsic elements such as characterization, plot, conflict, and setting. Extrinsic elements, namely psychological theories, through the perspective of psychoanalysis, are used to find out the factors that cause the character changes to occur in the main character. Other findings in this research also include character change caused by an event and interaction with other individuals.Keywords: Changes of Character; Main Character; Change Factor.